1984
DOI: 10.1002/j.1460-2075.1984.tb02198.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue polypeptide antigen (TPA) is related to the non-epidermal keratins 8, 18 and 19 typical of simple and non-squamous epithelia: re-evaluation of a human tumor marker.

Abstract: Because of the broad clinical interest which tissue polypeptide antigen (TPA) has attracted as a tumor marker, human cell lines and human tissues have been analyzed for TPA expression using immunofluorescence microscopy. Epithelial cell lines including HeLa, MCF‐7, and A‐431 are recognized by TPA antibodies whereas human lines of non‐epithelial origin are not. The positive staining patterns coincide with keratin‐type intermediate filaments of the cytoskeleton. On tissue sections a subset of epithelial cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(50 citation statements)
references
References 38 publications
4
46
0
Order By: Relevance
“…The staining appears as a diffuse network for the entire cell population. A similar pattern was observed for both antigens which was expected due to the homology between TPA and cytokeratins (Weber et al, 1984) Figure 6c shows the immunolocalization of CEA in cell cultures of similar passage. All cells appeared positive for CEA, although not all of them show the same stain intensity.…”
Section: Immunocytochemistrysupporting
confidence: 81%
“…The staining appears as a diffuse network for the entire cell population. A similar pattern was observed for both antigens which was expected due to the homology between TPA and cytokeratins (Weber et al, 1984) Figure 6c shows the immunolocalization of CEA in cell cultures of similar passage. All cells appeared positive for CEA, although not all of them show the same stain intensity.…”
Section: Immunocytochemistrysupporting
confidence: 81%
“…It was also noted that most breast carcinomas express phenotypic markers that are consistent with luminal origin. Furthermore, Weber et al [25] have colocalized the proposed tumor marker for breast cancer, tissue polypeptide antigen (TPA) with known cytoskeletal components such as cytokeratins 8, 18 and 19. Another study [26] has found specific staining for cytokeratin 7 and 20 in a study of 127 tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Deletion analysis coupled with the known lamin caspase cleavage site (43,44) pointed to Asp-237 as a cleavage site that was verified by the inability of caspases to cleave K18 Asp-237 3 Glu (42). Interestingly, keratin fragments have been identified in sera of patients who harbor any one of a variety of epithelial tumors (45,46) and may have diagnostic potential (47).…”
Section: Discussionmentioning
confidence: 99%